Shorter All-oral Bedaquiline-containing MDR-TB Regimen : The Backgrounds & Implementations - Winoto, Eden Suryoiman; Candradikusuma, Didi (Clinical and Research Journal in Internal Medicine, 2021)
The continuing spread of Multidrug-Resistant Tuberculosis (MDR-TB), which is defined as TB that shows resistance to both isoniazid and rifampicin, become one of the most urgent and difficult challenges in TB control. In Indonesia, the estimated total DR-TB case incidence of 24,000 or 8.8/100,000 population (2.4% of total new TB patients). The first-ever MDR-TB treatment guideline published by WHO required a long duration (up to 20â€“24 months) and contained toxic second-line drugs with less effective & unfavorable outcomes. About ten years ago, a short regimen lasting nine instead of 20 months, called â€œBangladesh regimenâ€, revolutionized MDR-TB treatment. The advent of rapid molecular diagnostic tests, discoveries of new and repurposed drugs, promising results based on trials and meta-analysis had prompted WHO to update its guidelines. Notably, drugs such as bedaquiline and clofazimine are now strongly recommended for the treatment of MDR-TB. At the same time, older injectables drugs have been downgraded due to poor effectiveness and side-effect profiles. In 2019, based on the programmatic data from the shorter all-oral bedaquiline-containing regimen implemented routinely in South Africa, WHO revised its recommendations on the use of a standardized shorter regimen. Based on the analysis, WHO affirmed its conditional recommendation for the shorter all-oral bedaquiline-containing MDR -TB regimen to be offered as a treatment option to MDR -TB patients who satisfy the eligibility criteria. The implementation of this all-oral shorter regimen is expected to improve the programmatic management of the MDR-TB worldwide.